Analysis Of The Effectiveness Of The Use Of Digital Platforms As A Promotional Strategy In The Development And Attraction Of Lon Malang Beach Tourism Sampang District - Halimatuz Zahro; Alan Su'ud Ma'adi; Taufiqur Rahman (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Lon Malang Beach is one of the tourist destinations that is starting to show its development. Lon Malang Beach is located in Sampang Regency, East Java, precisely in Bira Tengah Village, Sokobanah District . The development of Lon Malang Beach tourism certainly cannot be separated from the participation of the government, village youth and also the surrounding community. Apart from that, the existence of a digital platform is also an effective promotional medium to be used to help the development of Lon Malang Beach tourism to become more rapid and have a higher attraction so that it is widely known by the public. Of course, when carrying out promotional activities, there are inhibiting factors involved. The aim of this research is to find out the effectiveness of using digital media platforms as a promotional strategy in efforts to develop and attract tourists to Lon Malang Beach and to find out the inhibiting factors in using digital media as promotional media. This type of research uses a qualitative descriptive approach. Data collection using observation, interviews, and documentation as well as data analysis techniques with steps including data reduction, data presentation, and drawing conclusions. The research results show that apart from promotion through word of mouth, the use of digital platforms as promotional media is an appropriate and effective strategy to use in attracting tourists ' attention , interest and desire to visit Lon Malang beach. At the interest and action stage, it is effective in disseminating information related to Lon Malang beach tourism. Even though carrying out promotional activities via digital platforms is effective, there are obstacles in creating content experienced by the management and creative team of Lon Malang beach tourism.